2013
DOI: 10.4314/ahs.v13i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight loss on markers of systemic inflammation in obese Saudi children with asthma

Abstract: Background: Weight loss studies were conducted in children without asthma have demonstrated a reduction in systemic inflammation. However, the impact of weight loss in the obese paediatric population with asthma has not been investigated. Objective: To measure the effects of weight loss on markers of systemic inflammation in obese children with bronchial asthma. Methods: Eighty obese children with bronchial asthma (42 boys, and 38 girls) with mean age 13.86± 3.21 years were divided into two equal groups. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
(36 reference statements)
1
40
0
Order By: Relevance
“…Confirming the impact of weight loss or body fat percentage on the inflammatory profile, especially in obese people (31,32), the findings of the present study showed that regular aerobic training for 12 weeks significantly reduced the inflammatory cytokines of obese women. Therefore, the significant reduction of IL-6 serum after 12 weeks aerobic training may be attributed to changes in weight and body fat percentage compared to pre-exercise levels.…”
Section: Discussionsupporting
confidence: 84%
“…Confirming the impact of weight loss or body fat percentage on the inflammatory profile, especially in obese people (31,32), the findings of the present study showed that regular aerobic training for 12 weeks significantly reduced the inflammatory cytokines of obese women. Therefore, the significant reduction of IL-6 serum after 12 weeks aerobic training may be attributed to changes in weight and body fat percentage compared to pre-exercise levels.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, renal arterial endothelial function was blunted when incubated in vitro with perirenal fat harvested from MetS pigs, and restored by TNF-α inhibitor, substantiating its injurious effect on the renal vasculature. [39] Weight loss improves both inflammatory (CRP, TNF-α, IL-6 and leptin) and anti-inflammatory (adiponectin) markers in human subjects[40, 41], and MetS rats treated with anti-inflammatory mycophenolate mofetil showed reduced systemic and renal inflammation and limited renal fibrosis. [35] Therefore, measures to control inflammation in MetS may be beneficial for the kidney.…”
Section: Inflammation and Insulin Resistancementioning
confidence: 99%
“…A few studies have specifically focused on the impact of weight-loss interventions in obese-asthmatic children (2;65;112) suggesting improvements in lung function, inflammatory biomarkers, and exercise-induced bronchoconstriction. However, these studies have several limitations, including small sample sizes and short follow-up time.…”
Section: Therapeutic Approachesmentioning
confidence: 99%